Strategic Inventories in a Supply Chain with Vertical Control and Downstream Cournot Competition - (:unkn) unknown (My University, 2016)
Strategic Inventory (SI) has been an area of increased interest in theoretical supply chain literature recently. Most of the work so far however, has only considered a supply chain without downstream competition between retailers. Competition is ubiquitous in most market situations, hence, interactions between SI and retailer competition merits study as a first step in bringing the conversations and insights from this stream of literature to the real world. We present here a two-period and a three-period model of one manufacturer supplying an identical product to two retailers who form a Cournot duopoly. We also study a Commitment contract, where the manufacturer commits to all the selling seasons’ wholesale prices at the beginning of the 1st period. Commitment contracts have been shown previously to eliminate SI carriage over two selling seasons in the absence of retailer competition. We aim to deduce if this type of contract has the same effect in the presence of downstream competition. We determine closed-form Nash Equilibrium decision variable values for each of these models using game-theoretic modeling, a price-dependent linear demand function, and backward induction. We find that, the introduction of downstream Cournot duopoly competition leads to lower profits for both the manufacturer and retailer. This holds, whether the number of selling season is two or three. Consumer Surplus is also uniformly lower under retailer competition, compared to a downstream monopoly supply chain. When we try to deduce the effect of SI carriage under Cournot duopoly competition, by comparing an SC with Cournot duopoly competition and SI allowed between periods, to a similar SC with a Cournot duopoly downstream and a static, repeating, one-shot game in each period, with no SI carried – we find again that manufacturer and retailer profits are both lower when SI carriage is allowed. This holds whether the number of selling seasons is two or three. Consumer Surplus is also lower uniformly over both two and three selling seasons. Under a Commitment contract, over two selling seasons, the manufacturer ends up with an advantage, making a higher profit with downstream retailer competition, than compared to supplying to a monopoly downstream under the same contract. The retailers, while competing as a Cournot duopoly, are not able to use the relative advantage that comes from a Commitment contract to make a higher profit, as they are, when the downstream is a single retailer monopoly. The consumer also is disadvantaged by the introduction of downstream Cournot competition under a Commitment contract. When we compare a manufacturer supplying to a Cournot duopoly downstream of retailers, with, and without a Commitment contract (dynamic ordering), we see that the manufacturer and consumer benefit under a Commitment contract, making higher profits, but the retailer is at a disadvantage. It would be an interesting extension of this work to generalize the results from two and three selling seasons, presented here, to the “n” period case. It would also be benefi-cial to run empirical studies in real-world supply chains to validate if and to what extent the insights developed by this kind of game-theoretic modeling hold in a real-world supply chain setting. Development of contracts that are more effective than a Commitment con-tract in coordinating this supply chain would be another possible area for further research.
Keywords: Competitive Inventory Strategy; Cournot Duopoly with Vertical Control; Game-Theoretic Supply Chain Modeling; Strategic Inventories in Supply Chains; Supply Chain Inventory Strategy; Vertical Control